The Effect of Dietary Protein and Water Temperatures on Performance of T. rendalli Juveniles Reared in Indoor Tanks - Musuka, C.G.; Likongwe, J.S.; Kang 'ombe, J.; Jere, W.W.L.; Mtethiwa, A.H. (Pakistan Journal of Nutrition, 2009)
An experiment was conducted at Bunda College of Agriculture, Lilongwe, Malawi for 14 weeks (from August to November 2005) to determine the combined effect of dietary protein (30 and 40%) and water temperatures (22.8, 26 and 30 °C) on the performance of Tilapia rendalli juveniles reared in eighteen 200-L tanks with stocking rates of 15 fish (average wt 9.25g/fish) per tank. Results showed that the treatment of 40% crude protein at 30 °C temperature produced significantly (p